Lexical Semantics of the Quran: Analysis of Paradigmatic Meaning of Language Politeness - Tafiati, Tafiati; Asrina, Asrina; Saputra, Ferry; Utami, Shinta Fitria (Institut Agama Islam Negeri Curup, 2022)
The purpose of this study was to reveal the lexical meanings of the words baligha, sadida, karima, ma'rufa, layyina, and maisura, which are contained in polite language phrases in the Quran: qaulan baligha, qaulan sadida, qaulan karima, qaulan ma'rufa, qaulan layyina, and qaulan maisura. The importance of revealing the lexical semantics is in order to find the right meaning of the phrases. The method used is descriptive-qualitative method with a paradigmatic approach and lexical meaning theory. The results showed that the term baligha has six meaning features, the word sadida has five meaning features, the word karima has twelve meaning features, the word ma'rufa has eight meaning features, the word layyina has seven meaning features, and the word maisura has six meaning features. From the perspective of the paradigmatic relation, the phrases qaulan baligha, qaulan sadida, qaulan karima, qaulan ma'rufa, qaulan layyina, and qaulan maisura are hyponyms in politeness of the Quran language.